Liberdade cidadã e a Questão do Negro na I República: caso do Vale do Paraíba Fluminense - Siqueira, José Jorge (Sankofa (São Paulo), 2012)
These are the initial thoughts of a research project developed by us in the Masters Program in Social History of Severino Sombra University, seeking to clarify aspects of the structural transformation of the regional society in the passage from slavery to capitalism and the republic. More precisely we are interested in countering the study of structural transformation regarding the types of relationships of members work, the peculiar form of concentration of capital and the formulation of social representations and practices, compared to what would be called the Question of Negro. We assume that the latter can only be understood with minimal radicalism is tied to those changes, explaining them, but also being explained by them – consequently, also removing it from a unique cultural, minorities, or merely occasional.